2002
DOI: 10.1021/om020578c
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Cross-Coupling Reactions of Allyl, Phenyl, Alkenyl, and Alkynyl Germatranes with Aryl Iodides

Abstract: The potential of using organogermatranes in palladium-catalyzed cross-coupling with aryl iodides has been investigated. We have found that organogermatranes are less reactive in this analogue of Stille coupling than trialkylorganostannanes; nevertheless activation by fluoride promotes the reaction. The hypervalent germanium species produced from the germatranes provide a more efficient and more easily handled reagent than trialkoxygermanium analogues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 35 publications
0
48
0
Order By: Relevance
“…Recently, Faller et al developed an analogous reagent, arylgermatrane. [5] Oshima and co-workers reported that organotriA C H T U N G T R E N N U N G (2-furyl)germanes act as efficient coupling reagents. [6] Although the former reagent is easy to prepare, it is not only highly toxic, but also not so high yielding.…”
mentioning
confidence: 99%
“…Recently, Faller et al developed an analogous reagent, arylgermatrane. [5] Oshima and co-workers reported that organotriA C H T U N G T R E N N U N G (2-furyl)germanes act as efficient coupling reagents. [6] Although the former reagent is easy to prepare, it is not only highly toxic, but also not so high yielding.…”
mentioning
confidence: 99%
“…Compound 140 did indeed give a moderate yield of the cross-coupled product, with 4-bromotoluene catalyzed by [Pd 2 (dba) 3 ] and PPh(o-Tol) 2 , although elevated temperatures were required (Table 9.25). Following this concept, alkynylgermatranes 141 were reported that were able to undergo cross-coupling with iodoarenes on activation with TBAF [365]. The alkynylgermatranes 141 were readily prepared from the corresponding alkynylgermanium trichlorides.…”
Section: Alkynylgermanium Alkynylsilver and Alkynylmanganese Reagentsmentioning
confidence: 99%
“…IV): the Suzuki-Miyaura reaction (Y ¼ B) [8][9][10][11]; the Migita-Kosugi-Stille reaction (Y ¼ Sn) [12][13][14][15]; the Sonogashira coupling reaction (Y ¼ Cu) [7,16,17]; the Kumada-Tamao-Corriu reaction (Y ¼ Mg) [18][19][20]; the Hiyama reaction (Y ¼ Si) [21][22][23][24]; and the Negishi coupling (Y ¼ Zn) [25][26][27]. Other organometallic and heteroatom species, Y ¼ Al, Ge, In, Ag, Te, S, have been also tested as reagents for the transmetallation step [28][29][30][31][32][33][34][35].…”
Section: Catalytic CXC Bond Formation Via the Reductive Elimination Pmentioning
confidence: 99%